BESAR RISIKO FAKTOR FISIOLOGIS DAN FAKTOR PERILAKU TERHADAP KEJADIAN SINDROM METABOLIK - Fany Septianti Murningtyas; Meirina Dwi Larasati; Ana Yuliah Rahmawati; Setyo Prihatin (Poltekkes Kemenkes Semarang, 2020)
Background: Metabolic syndrome (MetS) is a risk factors for metabolic disorders such as high levels of triglyceride, blood sugar, blood pressure, central obesity and the low of HDL(NCEP-ATP III criteria). These risk factors are important to detect earlier. The worldwide prevalence of MetS were increased up to 20 – 25% and based on Riskesdas data from 2013 to 2018, the prevalence of MetS component were increased.Objective: To examine the risk of physiology and behavioral factors towards MetS incidents in Tlogosari Kulon PHC area.Method: An observational research with case-control design which involved 50 sampels aged 25 – 65 years in Tlogosari Kulon PHC area. Physiology factors were included gender, age, and genetic history which were collected through interview. Nutritional status based on anthropometric measurement, meanwhile the behavioral factors, including physical activities which were collected using an IPAQ and the knowledge factors were collected through 20 question which were collected by interview. Triglyceride, fasting blood sugar and HDL were measured using a spectrophotometer. Statistical analysis were used Chi-Square and Logistic Regression.Result: The chi-square test showed that there were significant relations between age (95% CI = 1,510 – 21,424; OR = 5,688), nutritional status (95% CI = 1,446 – 17,922; OR = 5,091), genetic history (95% CI = 1,170 – 12,194; OR = 3,778) and physical activity (95% CI = 1,180 – 12,606; OR = 3.857) with MetS incidents (p0,05). The logistic regression test showed that age (95% CI = 1,271 – 33,256; OR = 6,502) and nutritional status (95% CI = 1,038 – 25,957; OR = 5,191) were the most dominant variables toward the MetS incidents. Physiology and behavioral factors were contributed 47,8% to the MetS incidents.Conclusion: Age and nutritional status affect MetS incidents in Tlogosari Kulon PHC area.